2000
DOI: 10.1086/315890
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐12 Regulates the Response to Chemotherapy in Experimental Visceral Leishmaniasis

Abstract: In experimental visceral leishmaniasis, interleukin (IL)-12 initiates control over Leishmania donovani via Th1 cell activation, interferon (IFN)-gamma secretion, and granuloma formation. Because the leishmanicidal effect of conventional therapy, pentavalent antimony (Sb), also requires T cells and endogenous IFN-gamma, we tested IL-12 as a determinant of host responsiveness to chemotherapy. L. donovani-challenged IL-12p35 gene knockout (KO) mice permitted uncontrolled hepatic infection and failed to respond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
123
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 37 publications
6
123
0
Order By: Relevance
“…All of these findings together with our study indicate a stoichiometric proportion of IFN-␥ requirement along with TNF-␣ and immunosuppressive cytokine like IL-10, which can dictate the outcome of the disease. There are reports that primary Th1 cell-mediated antileishmanial events induced in IL-10 Ϫ/Ϫ mice require IFN-␥ that is largely induced by IL-12 (70). In our study IL-12 was completely down-regulated in the AG83-and GE1F8R-infected and blank vector-immunized hamster, whereas high levels of IL-12 mRNA transcripts were found in KMP-11 vaccinated hamsters.…”
Section: Discussionsupporting
confidence: 38%
“…All of these findings together with our study indicate a stoichiometric proportion of IFN-␥ requirement along with TNF-␣ and immunosuppressive cytokine like IL-10, which can dictate the outcome of the disease. There are reports that primary Th1 cell-mediated antileishmanial events induced in IL-10 Ϫ/Ϫ mice require IFN-␥ that is largely induced by IL-12 (70). In our study IL-12 was completely down-regulated in the AG83-and GE1F8R-infected and blank vector-immunized hamster, whereas high levels of IL-12 mRNA transcripts were found in KMP-11 vaccinated hamsters.…”
Section: Discussionsupporting
confidence: 38%
“…Infection with Sb R LD was associated with depressed Ag-specific T cell responses, decreased IL-12, TNF-a, and IFN-g production, and upregulation of suppressive cytokines IL-10 and TGF-b in an animal model of VL (24,28). SSG with imipramine was found to be effective to mount anti-SLA-specific T cell expansion, coupled with generation of IL-12 and suppression of IL-10 ( Fig.…”
Section: Discussionmentioning
confidence: 92%
“…IL-12 is the key cytokine for the initiation and maintenance of Th1 responses and IFN-g production from Th1 cells (26,55). Endogenous IL-12 is also required for the expression of the leishmanicidal effect of conventional chemotherapy (28). Having established that imipramine is a potent inhibitor of MDR-1, we studied its efficacy in combination with SSG to clear Sb R LD from the organs of infected mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, MG formation has been associated with clearance of Leishmania infection (36). An earlier report also suggested that the level of IL-12 might act as a critical factor in determining the nature of granuloma formation during experimental infection with VL (47). Because a parasite would not like to kill its host for the sake of its own survival, it is tempting to speculate that early activation of IL-12 and delayed activation of IL-10 in Sb R LD infection might be instrumental for survival of resistant parasites in the infected host.…”
Section: /2mentioning
confidence: 96%